1995
DOI: 10.1159/000244256
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor I Absorption in the Jejunum of Neonatal Calves

Abstract: The absorption of recombinant human insulin-like growth factor I (rhIGF-I), [125I]rhIGF-I, xylose and [3H]lysine, administered into a clamped jejunal segment in anesthetized neonatal calves, was studied by measuring their appearance in the mesenteric vein draining the gut segment. Only trace amounts of IGF-I and of [125I]rhIGF-I and/or 125I were absorbed following dissolution in saline, buffer or colostrum. The absorption rate of both [3H]lysine and/or 3H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
2
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 17 publications
6
38
2
8
Order By: Relevance
“…One could speculate that colostral IGF-I was intestinally absorbed and that Dexa treatment might have stimulated the absorption of colostral IGF-I, thus resulting in reduced hepatic IGF-I expression in colostrum-fed calves because of feedback inhibition (20,38). However, there was no evidence for increased absorption of macromolecules like IgG in Dexa-treated calves (Sauter SN, Blum JW, and Hammon HM, unpublished observation), and we could not demonstrate significant absorption of IGF-I in neonatal calves (20,50), although receptors for IGF-I are present in intestinal mucosa (18,22). Different feeding may influence hepatic IGF-I mRNA stability after Dexa treatment and may regulate IGF-I production at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…One could speculate that colostral IGF-I was intestinally absorbed and that Dexa treatment might have stimulated the absorption of colostral IGF-I, thus resulting in reduced hepatic IGF-I expression in colostrum-fed calves because of feedback inhibition (20,38). However, there was no evidence for increased absorption of macromolecules like IgG in Dexa-treated calves (Sauter SN, Blum JW, and Hammon HM, unpublished observation), and we could not demonstrate significant absorption of IGF-I in neonatal calves (20,50), although receptors for IGF-I are present in intestinal mucosa (18,22). Different feeding may influence hepatic IGF-I mRNA stability after Dexa treatment and may regulate IGF-I production at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 59%
“…Although colostral IGF-I did not affect systemic IGF-I levels in a significant manner, colostrum intake increased IGF-I plasma concentrations and hepatic IGF-I expression in neonatal calves, whereas GH plasma concentrations behaved inconsistently with respect to colostrum feeding (13,20,23,50). Besides the large nutrient supply by colostrum feeding, nonnutritive components of colostrum seem to affect the IGF-I status in neonatal calves (13).…”
mentioning
confidence: 86%
“…Colostral IGF-I is not absorbed in signifi cant amounts [84,85], probably due to interactions with colostral IGFBPs [85]. Because of low rate of absorption, colostral IGF-I ingestion has a minor infl uence on overall systemic growth and development, but has a strong impact on the neonatal digestive tract development.…”
Section: Igf Systemmentioning
confidence: 99%
“…There are controversies on the ability to penetrate the gut tissue and appearance of milk bioactive peptides in the circulating blood. Thornburg and Koldovsky (1987), Rao (1991), Xu and Wang (1996), Shen and Xu (2000) have found the gut permeable to numerous milk hormones and growth factors (insulin, IGF-I), on the other hand Griitter and Blum (1991), Vacher et al (1995), Donovan et al (1997) and Hadorn et al (1997), observed no absorption of insulin, prolactin and IGF-I from the gut lumen into the general circulation in newborns. The discrepancy among different reports may be due to different media used to deliver the bioactive peptides (colostrum vs milk formula) since Sangild et al (1999) reported that colostrum promotes the intestinal absorption of macromolecules.…”
Section: Role Of Bioactive Peptides Present In Milk For the Sucklingmentioning
confidence: 99%